The Button to Make Poverty History & How to Double Your Donation - Givel, Reto (Ethical theory and moral practice, 2007)
Even if together we could make poverty history, we would not all do our part. The paper presents a device that makes it more likely for everybody to do his part. This is achieved by making everybody’s contribution dependent on the other people’s commitment to contribute given that certain conditions are fulfilled. Furthermore, a device is introduced which, based on the same general idea, doubles everybody’s donation. Finally, possibilities, assumptions and limitations of such devices are addressed.